Stress and its associated factors among caregiver of cancer patient attending a selected hospital, Nepal - Giri, Prabina; Gahatraj, Nandram; Thapa, Shristi (Nepal Mediciti Medical Journal, 2025)
INTRODUCTION The study aims to assess the level of stress and contributing factor among the caregiver of cancer patients attending a selected hospital, Nepal.METHODS Quantitative method and cross-sectional study design was used to assess the level of stress among caregiver of cancer patients. The Interview questionnaire schedule was used as a data collection tool and data was collected using Kingston Care Giver Stress Scale and Caregiver Burden Inventory. Written consent was taken from the all participants.RESULTS The majority of the participants had experienced moderate stress 60.1% followed by mild stress 21.7% and severe stress 4.3%. The socio-demographic and socio-economic variables is not significantly associated with stress. Cancer patients and caregiver related variables like duration of illness 0.077 (p